2022
DOI: 10.3390/v14030585
|View full text |Cite
|
Sign up to set email alerts
|

Viral Shrimp Diseases Listed by the OIE: A Review

Abstract: Shrimp is one of the most valuable aquaculture species globally, and the most internationally traded seafood product. Consequently, shrimp aquaculture practices have received increasing attention due to their high value and levels of demand, and this has contributed to economic growth in many developing countries. The global production of shrimp reached approximately 6.5 million t in 2019 and the shrimp aquaculture industry has consequently become a large-scale operation. However, the expansion of shrimp aquac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 223 publications
1
21
0
Order By: Relevance
“…Shrimps, including the current target species, Exopalaemon carinicauda, are rich in proteins, amino acids, fat, vitamins and minerals (Liu et al, 2021), which help to enhance immunity and antioxidation, as well as to protect the cardiovascular function, thus leading to an increase in global shrimp aquaculture production for human consumption (Lai et al, 2023). However, in recent years, shrimp farming has been seriously affected due to the prevalence of shrimp diseases caused by pathogens including viruses (i.e., the White spot syndrome virus (WSSV), Taura syndrome virus (TSV), Infectious hypodermal and hematopoietic necrosis virus (IHHNV), and Hepatopancreatic parvovirus (HPV)) (Lee et al, 2022), bacteria (i.e., Aeromonas veronii, A. hydrophila, Vibrio parahaemolyticus and V. anguillarum) and fungi (i.e., Fusarium spp., Enterocytozoon hepatopenaei (Tourtip, 2009), Saprolegnia parasitica (Coker, 1935) and Achlya flagellata (Coker, 1935)) (Seethalakshmi et al, 2021). In addition, antibiotics and chemotherapeutics, which are typically applied to control diseases caused by harmful bacteria, were explicitly prohibited in aquaculture in 2019 (Lai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Shrimps, including the current target species, Exopalaemon carinicauda, are rich in proteins, amino acids, fat, vitamins and minerals (Liu et al, 2021), which help to enhance immunity and antioxidation, as well as to protect the cardiovascular function, thus leading to an increase in global shrimp aquaculture production for human consumption (Lai et al, 2023). However, in recent years, shrimp farming has been seriously affected due to the prevalence of shrimp diseases caused by pathogens including viruses (i.e., the White spot syndrome virus (WSSV), Taura syndrome virus (TSV), Infectious hypodermal and hematopoietic necrosis virus (IHHNV), and Hepatopancreatic parvovirus (HPV)) (Lee et al, 2022), bacteria (i.e., Aeromonas veronii, A. hydrophila, Vibrio parahaemolyticus and V. anguillarum) and fungi (i.e., Fusarium spp., Enterocytozoon hepatopenaei (Tourtip, 2009), Saprolegnia parasitica (Coker, 1935) and Achlya flagellata (Coker, 1935)) (Seethalakshmi et al, 2021). In addition, antibiotics and chemotherapeutics, which are typically applied to control diseases caused by harmful bacteria, were explicitly prohibited in aquaculture in 2019 (Lai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While many viruses can cause disease in farmed shrimp [34], two shrimp viruses, namely white spot syndrome virus and yellow head virus, are the major causes of economic loss to the shrimp aquaculture industry in many Asian countries, including Thailand [34,35]. Previous research has reported that a range of molecules including natural compounds, recombinant proteins, virus-like particles (VLPs), DNA vaccines, and specific double-stranded RNAs could all suppress viral replication or prevent viral infection in shrimp [13,36].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, P. vannamei farming is constantly hampered by abiotic and biotic factors [ 58 ]. One of the challenges faced by P. vannamei farming relates to emerging diseases caused by bacteria, viruses, and fungi affecting the sustainability of shrimp [ 1 , 31 , 32 ]. Antibiotics are used to prevent the growth of microbial infections, but the spread of microbial antibiotic resistance poses a hazard to human health [ 5 ].…”
Section: Introductionmentioning
confidence: 99%